Review on water evaporative cooling low-cost devices for tomato fruit preservation - Meli Viannie Ingrid, Kenne; Mbetmi Guy-de-patience , Ftatsi; Taga Cybèle , Maka; Nono Yvette , Jiokap (International Journal of Engineering and Technology, 2024)
In order to reduce post-harvest losses and ensure the availability of fresh tomatoes during the lean period to agro-industrial companies, farmers and those who market them, it is essential to find an inexpensive way to preserve them. Energy, environmental and economic issues lead us to seek solutions adapted to the context. Inexpensive means of conservation include water evaporative cooling systems. The aim of this article was to review the scientific, technical and legal aspects of existing evaporative preservation devices to ensure a continuous supply of this fruit. From our research and the field study, it appears that “pot-in-pot” technologies and evaporative cooling chambers (ECC) are deployed but still present several limitations, particularly in terms of storage time, adaptation to certain environments, device mass, mold growth; which justifies the fact that they are not yet adopted by many tomatoes’ farmers. Perspectives have been proposed to overcome the limitations of these devices.